The survivor [large type] : a Mitch Rapp novel - Flynn, Vince, 1966-2013; Flynn, Vince, 1966-2013 (Flynn, Vince, 1966-2013. Mitch Rapp novel., 2015)
"Top secret data has been stolen from the CIA, and the only man who knew its hiding place is dead. CIA operative Mitch Rapp must race to find the classified information before it falls into the wrong hands"